Blockchain in the industrial Internet of things - Ramasamy, Lakshmana Kumar; Kadry, Seifedine 1977- (IOP Publishing, 2021)
Blockchain and the Internet of Things (IoT) are separately regarded as highly capable popular technologies. Blockchain is a database used for decentralized transaction purposes. It provides novel directions to store and manage data, whereas the IoT relates to the propagation of linked smart machines through the Internet. A technology significant to the manufacturing business, which is currently experiencing a digital revolution through new equipment and data, leading to the Industrial Internet of Things, or the IIoT. The IIoT has advanced swiftly, but privacy issues and safety vulnerabilities remain concerns. Incorporating blockchain technology with its decentralization and embedded cryptographic principles with the IIoT creates Blockchain for Industrial Internet of Things (BIIoT) which can overcome these security requirements and motivate the further development of Industry 4.0. This book gives a detailed survey of BIIoT and discusses all relevant aspects of this concept, including structural design and open research directions
Keywords: Distributed databases; COMPUTERS / Blockchain; Blockchains (Databases); Internet of things